Money and banking - Dean Croushore (Houghton Mifflin Co., 2007)
Combining a concise writing style with real-world applications, this innovative text takes a new approach to the money and banking course. Money and Banking examines the role the banking system plays in individual financial activities and considers the monetary policymaking that shapes the world's financial system. A highly respected teacher--and a leading expert on macroeconomic forecasting, with several years of experience at the Federal level--Croushore makes the personal and the public relevant and interesting to students. The text's shorter, more focused approach addresses the modern framework of today's financial system, in which both financial markets and banks play important roles. Designed to appeal to a range of learners, the pedagogical features include over 130 figures and 20 full-color photos and cartoons. The ancillary program, written entirely by the author, provides a well-integrated set of learning tools and teaching resources